1992
DOI: 10.1080/15287399209531686
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid effects of coal‐derived pollutants

Abstract: Endemic goiter in iodide-sufficient areas of the United States and Colombia has been linked to watersheds rich in coal and shale, which several reports suggest are the source of water-borne goitrogens. In this report the potential antithyroid activities of aqueous coal and shale extracts and of compounds identified in aqueous effluents from coal conversion processes were assayed in thyroid peroxidase (TPO) and thyroid slice systems. Aqueous extracts of coal and black shale were potent inhibitors of TPO or 125I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 27 publications
0
6
0
3
Order By: Relevance
“…The pollutants are organics produced from coal and found in air and water. In their study they found that these pollutants have potent anti-thyroid effects [45]. Two populations of school children from different geographical locations showed a high prevalence of goiter in equally iodine-sufficient areas [46].…”
Section: Nodh2h4 and Other Environmental Influencesmentioning
confidence: 99%
“…The pollutants are organics produced from coal and found in air and water. In their study they found that these pollutants have potent anti-thyroid effects [45]. Two populations of school children from different geographical locations showed a high prevalence of goiter in equally iodine-sufficient areas [46].…”
Section: Nodh2h4 and Other Environmental Influencesmentioning
confidence: 99%
“…В исследовании, проведенном Lindsay et al, изу чалась возможная антитиреоидная активность оса дочных пород угля и глинистого сланца. Оказалось, что осадочные породы угля и глинистого сланца яв ляются ингибиторами тиреоидной пероксидазы и органификации 125 I [30]. Gaitan E. et al исследовали антитиреоидные эф фекты экстрактов каменного угля у крыс после ост рого и хронического их перорального введения.…”
Section: экстракты каменного угляunclassified
“…Iodide dietary supplementation programs have had only partial success against goitre; consequently, iodide lack cannot be seen as the only causative factor for goitre endemia. It has been shown that there are some connections between the origin of water and the incidence of goitre (Lindsay, 1997). Poor quality drinking water has been known for years to be associated with goitre (Gaitan, 1983;Ubom, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This anomaly has been attributed to the presence of goitrogens, which prevent the thyroid from being able to use the iodide (Gaitan, 1983). Endemic goitre in iodide-sufficient areas of the USA and Columbia has been linked to water-soluble goitrogens (Lindsay et al, 1997) such as compounds derived from coal; 2-and 5-methyl resorcinol. Other compounds with less potent activity include thiocyanates, disulphides and hydroxypyridines.…”
Section: Introductionmentioning
confidence: 99%